External validity of clinical trials with diverse trastuzumab-based chemotherapy regimens in advanced gastroesophageal adenocarcinoma: data from the AGAMENON-SEOM registry. (June 2021) - Jimenez-Fonseca, Paula; Carmona-Bayonas, Alberto; Martinez-Torron, Alba; Alsina, Maria; Custodio, Ana; Serra, Olbia; Cacho Lavin, Diego; Limón, María Luisa; Sauri, Tamara; López, Flora; Visa, Laura; Granja, Mónica; et al.
Background: Trastuzumab combined with cisplatin and fluoropyrimidines, either capecitabine or 5-fluorouracile (XP/FP), is the standard first-line treatment for advanced, HER2-positive, gastric cancer patients based on the ToGA trial. Despite the lack of phase III trials, many clinicians administer trastuzumab with alternative regimens. One meta-analysis suggests that substituting cisplatin for oxaliplatin might lead to greater efficacy and less toxicity. Methods: 594 patients with HER2-positive gastroesophageal adenocarcinoma were recruited from the AGAMENON-SEOM registry. The objective was to evaluate the external validity of clinical trials with chemotherapy and trastuzumab. Results: The regimens used in at least 5% of the patients were XP (27%), oxaliplatin and capecitabine (CAPOX) (26%), oxaliplatin and 5-fluorouracil (FOLFOX) (14%), FP (14%), triplet with anthracycline/docetaxel (7%), and carboplatin-FU (5%). Median exposure to trastuzumab was longer with FOLFOX (11.4 months, 95% CI, 9.1–21.0) versus ToGA regimens (7.5, 6.4–8.5), p  < 0.001. Patients with HER2-IHC 3+ cancers had higher response rates than those with IHC 2+/FISH+, odds-ratio 1.97 (95% CI, 1.25–3.09). The results achieved with CAPOX–trastuzumab were comparable to those attained with ToGA regimens. FOLFOX–trastuzumab was superior to ToGA schemes in terms of overall survival (OS), with a greater magnitude of effect in IHC 2+/FISH+ tumors (HR 0.47, 0.24–0.92) compared with IHC 3+ (HR 0.69, 0.49–0.96), and in diffuse (HR 0.37, 0.20–0.69) versus intestinal-type tumors (HR 0.76, 0.54–1.06). Conclusion: We have updated the external validity of clinical trials with trastuzumab in first-line treatment of gastric cancer. Our data confirm the comparable outcomes of ToGA regimens and CAPOX–trastuzumab in clinical practice and point toward a possible benefit of FOLFOX–trastuzumab, contingent on the subtypes typically less sensitive to trastuzumab, to be confirmed in clinical trials.